A Project Report on Air Bag Deployment and Postcrash Distress Signal Generation at High-G Landing of a Helicopter - SHIVA PRASAD, SOMASHEKHAR, SRINIDHI and RAVI N (2003)
INTERNAL GUIDE: PADMINI, MVJCE EXTERNAL GUIDE: SRINIVASA MURTHY, MANAGER RWR ANDDC HAL
Keywords: High-G Landing of a Helicopter